Integrating Politeness Principles and Strategies in Counselling Technique: A Phenomenological Study - Syafryadin, Syafryadin (Journal of Pragmatics Research, 2021)
Politeness is an important academic topic. An action must be taken to prevent rudeness. As a result, this study investigates how counseling techniques can modify students' behavior to be more courteous by implementing politeness tactics and concepts. Furthermore, the purpose of this study is to determine why counseling strategies may alter students' perspectives. The research was conducted using a phenomenological study using an observation checklist and interview guideline. The instruments were triangulated for validity. Data collection, data condensation, data display, and conclusion were all used in the data analysis. The findings revealed that Counselling Technique could have an impact on the outcome. The findings revealed that Counselling Technique had the ability to change students' conduct to become more polite. The students used negative politeness methods to consult with the instructors during its execution. Furthermore, students used all of the politeness standards, including the tact principle, generosity principle, modesty principle, approval principle, compassion principle, and agreement principle. In summary, the counseling strategy could be employed to help pupils with their behavioral issuesKeywords: Politeness principles, strategies; counselling technique, Phenomenological study